Exchange Rate Volatility and Exports: The Nigerian Scenario - Duru, Innocent U; Eze, Millicent Adanne; Saleh, Abubakar Sadiq; Uzoechina, Benedict I; Ebenyi, Gabriel O; Chukwuka, Ekechi (Asian Journal of Empirical Research, 2022)
This paper investigated the impact of exchange rate volatility on exports in Nigeria utilizing data from 2005Q1 to 2020Q4. The ARCH model and its extensions of GARCH, TARCH and EGARCH models and nominal effective exchange rate were employed to measure exchange rate volatility. The Autoregressive Distributed Lag Bounds test methodology was used to examine the short-run and long-run effects of exchange rate volatility on exports. The findings validated the presence of exchange rate volatility. In addition, the results revealed that exchange rate volatility had a negative and insignificant impact on exports. The study, thus, recommends that the government of Nigeria through the Central Bank of Nigeria should foster stable regimes of exchange rate through the implementation of appropriate policies of the exchange rate. Also, an enabling environment for the production of exportable goods should be provided by the government.